Fluorescent natural rubber composite material and preparation method thereof
By mixing organic luminescent crystals with natural rubber matrix and performing specific preparation treatments, the problem of improving the performance of existing fluorescent natural rubber composites is solved, and the fluorescence performance and performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202411698314.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-26
AI Technical Summary
In the existing fluorescent natural rubber composite materials, the added luminescent elements only impart the material's fluorescent performance, but have not participated in the adjustment and changes of the rubber material's performance, and have failed to improve the performance of natural rubber composite materials.
The organic luminescent crystals are mixed with a natural rubber matrix and fluorescent natural rubber composites are prepared by specific preparation methods, including kneading, calendering and vulcanization.
It not only imparts fluorescent properties to the material, but also improves its tensile strength, fracture properties and wear resistance through its interaction with natural rubber.
Smart Images

Figure CN119431907A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the rubber-related field, and particularly relates to a fluorescent natural rubber composite material and a preparation method thereof. Background Art
[0002] Natural rubber composites with fluorescent properties combine the excellent elasticity of rubber and the unique optical properties of fluorescent substances. This type of new material shows broad application potential in security marking, environmental monitoring, biosensing, artistic decoration and other fields.
[0003] In the preparation of fluorescent natural rubber composite materials, the selection of luminescent primitives is crucial. The existing natural rubber luminescent primitives are basically selected from common luminescent additives, inorganic phosphors, carbon-based nanomaterials, etc., and are prepared by solvent blending, in-situ polymerization, surface grafting, nanoparticle doping, etc. However, no matter which luminescent primitive is used or which preparation method is adopted, the added luminescent primitive only gives the material fluorescent properties, and does not participate in the adjustment and change of the rubber material properties, and does not improve the performance of the natural rubber composite material. For example, Chinese patent application number CN201910683682.3 discloses a luminous tire and its processing technology, the raw materials include isoprene rubber, natural rubber, butadiene rubber, ethylene propylene diene rubber, white carbon black, rubber operating oil, zinc oxide, stearic acid, active agent, protective wax, antioxidant, phosphor, accelerator, sulfur; accelerators include accelerator TMTD, accelerator CZ and accelerator BZ. The tire prepared by the above raw materials can not only glow at night, but also maintain the original good wear resistance of the tire. For example, the scientific document "Synthetic Rubber Industry, 2005-11-15, 28(6):432-434" discloses the preparation and properties of fluorescent rubber. In the section "2.1.4 Effect of fluorescent powder on fluorescent properties", it is clearly stated that "the amount of fluorescent powder has little effect on the mechanical properties of fluorescent rubber, but as the amount of fluorescent powder increases, the fluorescent effect of fluorescent rubber increases." Summary of the invention
[0004] Therefore, the object of the present invention is to provide a fluorescent natural rubber composite material to solve the problem that the added luminescent element in the fluorescent natural rubber composite material prepared by using the traditional luminescent element only gives the composite material fluorescent properties, does not participate in the adjustment and change of the properties of the rubber material, and does not improve the performance of the natural rubber composite material.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A fluorescent natural rubber composite material comprises the following raw materials in parts by weight: 100 parts of natural rubber, 0.1-1 parts of stearic acid, 2-7 parts of zinc oxide, 0.3-1.2 parts of accelerator M, 1-6 parts of sulfur and 0.1-2 parts of organic luminescent crystals.
[0007] In an optional embodiment, the organic light-emitting crystal is organic light-emitting crystal A or organic light-emitting crystal B.
[0008] In an optional embodiment, the preparation process of the organic luminescent crystal A includes the following steps: dissolving 2,5-dimethoxyacyl-1,4-cyclohexanedione in methanol to obtain a suspension, adding n-pentylamine to the suspension, stirring to obtain a mixed solution, cooling, filtering and concentrating the mixed solution to obtain a red powder, dissolving the red powder in a solvent, and cultivating the organic luminescent crystal A by a solvent diffusion method, wherein the organic luminescent crystal A is dimethyl 2,5-di(pentylamine) terephthalate.
[0009] In an optional embodiment, the preparation process of the organic luminescent crystal B includes the following steps: dissolving 2,5-dimethoxyacyl-1,4-cyclohexanedione in methanol to obtain a suspension, adding 3-amino-1-propanol to the suspension, stirring to obtain a mixed solution, cooling, filtering and concentrating the mixed solution to obtain a red powder, dissolving the red powder in an organic solvent, and cultivating the organic luminescent crystal B by a solvent diffusion method, wherein the organic luminescent crystal B is dimethyl 2,5-di(3-hydroxypropyl)terephthalate.
[0010] In an optional embodiment, the mass ratio of the 2,5-dimethoxyacyl-1,4-cyclohexanedione to n-pentylamine is 1:3-4.
[0011] In an optional embodiment, the mass ratio of the 2,5-dimethoxyacyl-1,4-cyclohexanedione to 3-amino-1-propanol is 1:3-4.
[0012] In an alternative embodiment, the organic solvent is a mixed solvent of dichloromethane and petroleum ether.
[0013] In an alternative embodiment, the organic solvent is a mixed solvent of methanol and cyclohexane.
[0014] The present invention also provides a method for preparing a fluorescent natural rubber composite material, comprising the following steps: mixing natural rubber, stearic acid, zinc oxide, accelerator M, sulfur and organic luminescent crystals on an open mill to mix the rubber and filler evenly, rolling out sheets, and vulcanizing at 120°C to 150°C to obtain the fluorescent natural rubber composite material.
[0015] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0016] 1. After the organic luminescent crystals are mixed with the natural rubber matrix, the present invention can not only give the natural rubber fluorescent properties, but also produce a certain interaction with the natural rubber, further improving the tensile strength, fracture performance and wear resistance of the natural rubber.
[0017] 2. The organic luminescent crystal of the present invention has low raw material cost, is green and environmentally friendly, can be synthesized by a simple one-step reaction and crystal engineering, and is suitable for large-scale application. The organic luminescent crystal has good dispersibility, modifiability, and biocompatibility in the natural rubber matrix, which can improve the composite effect with the rubber matrix, and can also be vulcanized together with natural rubber without increasing processing steps and costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The fluorescence spectrum of the organic luminescent crystal A and the fluorescent natural rubber composite material (the organic luminescent crystal is the organic luminescent crystal A) according to an embodiment of the present invention;
[0019] Figure 2 This is a comparison chart of the tensile strength of the natural rubber composite material and the fluorescent natural rubber composite material (the organic luminescent crystal is the organic luminescent crystal A) according to the embodiment of the present invention;
[0020] Figure 3 This is a comparison diagram of the fracture energy of the natural rubber composite material and the fluorescent natural rubber composite material (the organic luminescent crystal is the organic luminescent crystal A) according to the embodiment of the present invention;
[0021] Figure 4 This is a comparison chart of the wear resistance of the natural rubber composite material of the embodiment of the present invention and the fluorescent natural rubber composite material (the organic light-emitting crystal is the organic light-emitting crystal A);
[0022] Figure 5 This is a hardness comparison diagram of the natural rubber composite material according to the embodiment of the present invention and the fluorescent natural rubber composite material (the organic light-emitting crystal is the organic light-emitting crystal B). DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0024] Example 1
[0025] (1) Preparation of organic light-emitting crystal A
[0026] The method comprises the following steps: firstly adding 1.2g of 2,5-dimethoxyacyl-1,4-cyclohexanedione and 30mL of methanol into a 100mL double-mouthed round-bottomed flask, adding 3.7g of n-pentylamine into the suspension, installing and fixing the round-bottomed flask with a rubber stopper and a spherical condenser, stirring at 60°C and open air at normal pressure for 10h to obtain a mixture, cooling the mixture to room temperature, pouring it into a Buchner funnel for suction filtration and collecting the filter cake, washing it with petroleum ether, concentrating the filtrate to obtain 1.60g (4.39mmol, 88%) of red powder, selecting dichloromethane and petroleum ether (volume ratio of 1:2) as solvents, and using a solvent diffusion method to cultivate an organic luminescent crystal A, wherein the organic luminescent crystal A is dimethyl 2,5-di(pentylamine) terephthalate (hereinafter referred to as DMPAP).
[0027] The chemical reaction formula is as follows:
[0028]
[0029] (2) Preparation of fluorescent natural rubber composites
[0030] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 0.2 g of organic luminescent crystal A are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered, and a sheet is vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-DMPAP-0.2).
[0031] Example 2
[0032] The preparation method of the fluorescent natural rubber composite material of this embodiment is the same as that of the above-mentioned embodiment 1, except for the addition amount of the organic luminescent crystal A. The addition amount of the organic luminescent crystal A of the fluorescent natural rubber composite material of this embodiment is 0.6 g.
[0033] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 0.6 g of organic luminescent crystal A are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered, and a sheet is vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-DMPAP-0.6).
[0034] Example 3
[0035] The preparation method of the fluorescent natural rubber composite material of this embodiment is the same as that of the above-mentioned embodiment 1, except for the addition amount of the organic luminescent crystal A. The addition amount of the organic luminescent crystal A of the fluorescent natural rubber composite material of this embodiment is 1 g.
[0036] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 1 g of organic luminescent crystal A are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered and vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-DMPAP-1).
[0037] Example 4
[0038] The preparation method of the fluorescent natural rubber composite material of this embodiment is the same as that of the above-mentioned embodiment 1, except for the addition amount of the organic luminescent crystal A. The addition amount of the organic luminescent crystal A of the fluorescent natural rubber composite material of this embodiment is 2 g.
[0039] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 2 g of organic luminescent crystal A are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered and vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-DMPAP-2).
[0040] Example 5
[0041] (1) Preparation of organic light-emitting crystal B
[0042] The method comprises the following steps: firstly adding 1.2 g of 2,5-dimethoxyacyl-1,4-cyclohexanedione and 30 mL of methanol into a 100 mL double-mouth round-bottom flask, adding 3.8 g of 3-amino-1-propanol into the suspension, installing and fixing the round-bottom flask with a rubber stopper and a spherical condenser, stirring at 60° C. and open air at normal pressure for 10 hours to obtain a mixture, cooling to room temperature, pouring the mixture into a Buchner funnel for suction filtration and collecting a filter cake, washing with petroleum ether, concentrating the filtrate to obtain 1.5 g (4.47 mmol, 86%) of a red powder, selecting methanol and cyclohexane (volume ratio of 1:2) as solvents, and using a solvent diffusion method to culture an organic light-emitting crystal B (hereinafter referred to as AMPRL).
[0043] The chemical reaction formula is as follows:
[0044]
[0045] (2) Preparation of fluorescent natural rubber composites
[0046] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 0.2 g of organic luminescent crystal B are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered, and a sheet is vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-AMPRL-0.2).
[0047] Example 6
[0048] The preparation method of the fluorescent natural rubber composite material of this embodiment is the same as that of the above-mentioned embodiment 5, except for the addition amount of the organic luminescent crystal B. The addition amount of the organic luminescent crystal B of the fluorescent natural rubber composite material of this embodiment is 0.6 g.
[0049] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 0.6 g of organic luminescent crystal A are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered, and a sheet is vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-AMPRL-0.6).
[0050] Example 7
[0051] The preparation method of the fluorescent natural rubber composite material of this embodiment is the same as that of the above-mentioned embodiment 5, except for the addition amount of the organic luminescent crystal B. The addition amount of the organic luminescent crystal B of the fluorescent natural rubber composite material of this embodiment is 1 g.
[0052] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mixing mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 1 g of organic luminescent crystal B are weighed respectively, and the mixture is mixed on the open mixing mill to uniformly mix the rubber material and the filler, and the mixture is rolled into sheets, and vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-AMPRL-1).
[0053] Example 8
[0054] The preparation method of the fluorescent natural rubber composite material of this embodiment is the same as that of the above-mentioned embodiment 5, except for the addition amount of the organic luminescent crystal B. The addition amount of the organic luminescent crystal B of the fluorescent natural rubber composite material of this embodiment is 2 g.
[0055] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 2 g of organic luminescent crystal B are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered and vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-AMPRL-2).
[0056] Comparative Example 1
[0057] A natural rubber composite material. Compared with Example 1, the natural rubber composite material of this comparative example does not contain organic luminescent crystal A. The preparation method thereof comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes. After plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), and 3 g of sulfur are weighed respectively, and mixed on an open mill to uniformly mix the rubber material and the filler, and the sheets are calendered and vulcanized at 145° C. to obtain a natural rubber composite material (hereinafter referred to as NR).
[0058] Comparative Example 2
[0059] A fluorescent natural rubber composite material. Compared with Example 1, the difference of the fluorescent natural rubber composite material in this comparative example is the addition amount of organic luminescent crystal A. The addition amount of organic luminescent crystal A in the fluorescent natural rubber composite material in this comparative example is 5g.
[0060] The method comprises the following steps: 100 g of raw rubber is plasticized on an open mill for 10 minutes, after the plasticization is uniform, 0.5 g of stearic acid, 5 g of zinc oxide, 0.7 g of accelerator M (2-mercaptobenzothiazole), 3 g of sulfur, and 5 g of organic luminescent crystal A are weighed respectively, and the mixture is mixed on the open mill to uniformly mix the rubber material and the filler, and a sheet is calendered and vulcanized at 145° C. to obtain a fluorescent natural rubber composite material (hereinafter referred to as NR-DMPAP-5).
[0061] Performance Testing
[0062] (I) Fluorescence performance detection
[0063] The DMPAP, NR-DMPAP-0.2, NR-DMPAP-0.6, NR-DMPAP-1, and NR-DMPAP-2 prepared in Examples 1-4 were subjected to fluorescence spectrum tests and fluorescence quantum efficiency tests at different locations (the experimental results were not affected by the location). The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the amount of DMPAP added has no effect on the fluorescence properties of NR, indicating that DMPAP can impart fluorescence properties to NR and the amount of addition has little effect on the fluorescence intensity.
[0064] (ii) Tensile strength test
[0065] The NR-DMPAP-0.2, NR-DMPAP-0.6, NR-DMPAP-1, NR-DMPAP-2 prepared in Examples 1-4, the NR prepared in Comparative Example 1, and the NR-DMPAP-5 prepared in Comparative Example 2 were tested using a universal tensile machine. The rubber was cut into dumbbell-shaped specimens with a center size of 25 mm×6 mm×1 mm in the calendering direction. The stress-strain curve was tested at a tensile rate of 500 mm / min at room temperature. The reference standard was GB / T528-2009. The results are as follows: Figure 2 As shown in Figure (a), Figure 2 Figure (a) is a stress-strain curve. The tensile strength test results are obtained by testing the stress-strain curve. Figure 2 As shown in Figure (b).
[0066] Depend on Figure 2 As shown in Figure (b), the original tensile strength of NR without any luminescent material is 17.57 MPa. When different amounts of DMPAP are added to NR, the overall tensile strength of NR increases first and then decreases with the increase in the amount of DMPAP added. Among them, when 0.6 phr DMPAP is added to NR, the tensile strength reaches a maximum value of 22.65 MPa. When 5 phr DMPAP is added to NR, the tensile strength decreases to 14.58 MPa, indicating that the amount of DMPAP added should be within an appropriate range. Exceeding this range will lead to a decrease in the tensile strength of NR.
[0067] (III) Fracture energy test
[0068] The NR-DMPAP-0.2, NR-DMPAP-0.6, NR-DMPAP-1, NR-DMPAP-2 prepared in Examples 1-4, the NR prepared in Comparative Example 1, and the NR-DMPAP-5 prepared in Comparative Example 2 were respectively subjected to fracture energy tests using a universal tensile machine. The fracture test was performed at a tensile rate of 6 mm / min at room temperature. The sample was a rectangular specimen of 20 mm×4 mm×1 mm. An edge notch with a length of 1 mm was preset in the middle of the specimen before the test. The fracture energy (Gc) was calculated using the following formula:
[0069]
[0070] The results are as follows Figure 3 As shown by Figure 3 As shown in Figure (a), the original fracture energy of NR without any luminescent material is 31.0 KJ / m 2When different amounts of DMPAP are added to NR, the elongation at break of NR increases first and then decreases with the increase of DMPAP addition, indicating that NR has good toughness after adding DMPAP. When 0.6phr DMPAP is added to NR, the fracture energy is 36.2KJ / m 2 This indicates that the fracture energy of NR can only be improved when a certain amount of DMPAP is added, and exceeding this amount will reduce the fracture energy of NR. Figure 3 As can be seen from Figure (b), when different amounts of DMPAP are added to NR, the average molecular weight of NR shows a trend of first decreasing and then increasing with the addition of DMPAP, indicating that the crosslinking density of NR first increases and then decreases with the addition of DMPAP, that is, the breaking energy first increases to a certain extent and then decreases with the increase of the addition of DMPAP.
[0071] (IV) Wear resistance test
[0072] The NR-DMPAP-0.2, NR-DMPAP-0.6, NR-DMPAP-1, NR-DMPAP-2 prepared in Examples 1-4, the NR prepared in Comparative Example 1, and the NR-DMPAP-5 prepared in Comparative Example 2 were respectively subjected to Akron abrasion tester JZ-6041, with the rubber wheel shaft rotating at 76 r / min and the grinding wheel shaft rotating at 35 r / min, and the density was measured in accordance with GB / T 1689-2014 to calculate the wear volume. The friction coefficient was measured using the UMT series multifunctional material mechanics testing system, with an applied force of 0.3 N, a test time of 1800 s, and a number of 100 turns. The friction coefficient is as follows Figure 4 As shown in Figure (a), the wear volume is Figure 4 As shown in Figure (b).
[0073] Depend on Figure 4 As shown in Figure (a), the friction coefficient of NR without any luminescent material is lower than that of NR with the luminescent material DMPAP added, indicating that adding DMPAP to NR can increase the hardness of NR, thereby improving the friction resistance of NR.
[0074] Depend on Figure 4 As shown in Figure (b), when different amounts of DMPAP are added to NR, the wear volume of NR shows a trend of first decreasing and then increasing with the increase of DMPAP addition. The original wear volume of NR without any luminescent material is 1.7 cm 3When DMPAP is added to NR, the overall wear performance of NR will be improved. NR with DMPAP has good wear resistance. When 1phrDMPAP is added, the wear loss is only 0.4cm 3 , which has the smallest wear amount among all the addition amounts.
[0075] (V) Hardness test
[0076] The NR-AMPRL-0.2, NR-AMPRL-0.6, NR-AMPRL-1, and NR-AMPRL-2 prepared in Examples 5 to 8 and the NR prepared in Comparative Example 1 were respectively tested for hardness using a Shore A rubber durometer. According to GBT531 "Test method for Shore A hardness of vulcanized rubber" as the test standard, the measuring force was 0.55N. A pressing needle with a preset load was pressed into the surface of the sample within a specified time. The maximum force during the measurement process was the hardness value. The results are shown in FIG. Figure 5 shown.
[0077] Depend on Figure 5 It can be seen that the hardness of NR without any luminescent material is 47ShoreA, and after adding the luminescent material AMPRL, the overall hardness of NR is significantly improved, and with the increase of AMPRL addition, the hardness gradually increases, indicating that the addition of AMPRL can improve the overall hardness of NR and make NR have good wear resistance.
[0078] Although the present invention has been described using the above preferred embodiments, it is not intended to limit the scope of protection of the present invention. Any person skilled in the art who makes various changes and modifications to the above embodiments without departing from the spirit and scope of the present invention still fall within the scope of protection of the present invention.
Claims
1. A fluorescent natural rubber composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of natural rubber, 0.1-1 parts of stearic acid, 2-7 parts of zinc oxide, 0.3-1.2 parts of accelerator M, 1-6 parts of sulfur and 0.1-2 parts of organic luminescent crystals.
2. The fluorescent natural rubber composite material according to claim 1, characterized in that: The organic light-emitting crystal is organic light-emitting crystal A or organic light-emitting crystal B.
3. The fluorescent natural rubber composite material according to claim 2, characterized in that: The preparation process of the organic luminescent crystal A comprises the following steps: dissolving 2,5-dimethoxyacyl-1,4-cyclohexanedione in methanol to obtain a suspension, adding n-pentylamine to the suspension, stirring to obtain a mixed solution, cooling, filtering and concentrating the mixed solution to obtain a red powder, dissolving the red powder in a solvent, and cultivating the organic luminescent crystal A by a solvent diffusion method. The organic luminescent crystal A is dimethyl 2,5-di(pentylamine) terephthalate.
4. The fluorescent natural rubber composite material according to claim 2, characterized in that: The preparation process of the organic luminescent crystal B comprises the following steps: dissolving 2,5-dimethoxyacyl-1,4-cyclohexanedione in methanol to obtain a suspension, adding 3-amino-1-propanol to the suspension, stirring to obtain a mixed solution, cooling, filtering and concentrating the mixed solution to obtain a red powder, dissolving the red powder in an organic solvent, and cultivating the organic luminescent crystal B by a solvent diffusion method. The organic luminescent crystal B is dimethyl 2,5-di(3-hydroxypropyl)terephthalate.
5. The fluorescent natural rubber composite material according to claim 3, characterized in that: The mass ratio of the 2,5-dimethoxyacyl-1,4-cyclohexanedione to n-pentylamine is 1:3-4.
6. The fluorescent natural rubber composite material according to claim 4, characterized in that: The mass ratio of the 2,5-dimethoxyacyl-1,4-cyclohexanedione to 3-amino-1-propanol is 1:3-4.
7. The fluorescent natural rubber composite material according to claim 3, characterized in that: The organic solvent is a mixed solvent of dichloromethane and petroleum ether.
8. The fluorescent natural rubber composite material according to claim 4, characterized in that: The organic solvent is a mixed solvent of methanol and cyclohexane.
9. The method for preparing the fluorescent natural rubber composite material according to claim 1, characterized in that: The following steps are involved: Natural rubber, stearic acid, zinc oxide, accelerator M, sulfur and organic luminescent crystals are mixed on an open mill to make the rubber and filler mixed evenly, and sheets are calendered and vulcanized at 120° C. to 150° C. to obtain a fluorescent natural rubber composite material.
Citation Information
Patent Citations
A luminous tire and its processing technology
CN110483854B
Preparation method of silicone rubber composite material with fluorescence
CN102604391A
Tire fluorescent sidewall rubber and preparation method
CN102964639A
Natural rubber foamed material and preparation method thereof
CN108084509A
Manufacturing method of luminous pet tennis ball
CN109485923A